Hidden potential : the science of achieving greater things - Grant, Adam, 1981- (Viking, 2023)
"The #1 New York Times bestselling author of Think Again illuminates how we can elevate ourselves and others to unexpected heights. We live in a world that's obsessed with talent. We celebrate gifted students in school, natural athletes in sports, and child prodigies in music. But admiring people who start out with innate advantages leads us to overlook the distance we ourselves can travel. We underestimate the range of skills that we can learn and the amount of ground that we can gain. When opportunity doesn't knock, there are ways to build a door. Hidden Potential offers a new framework for reaching aspirations and exceeding expectations. Realizing potential isn't about being a workaholic or a perfectionist. What matters most is not how hard we work, but how well we learn. It's not about being a genius-growth depends more on developing character skills than cognitive skills. The character skills that propel progress include the proactivity to absorb and adapt to new information, the courage to embrace discomfort, and the determination to find the beauty in imperfections. Mastering those skills doesn't require us to find the one perfect mentor or expert coach to guide us. Often we just need to borrow a compass to begin charting our own path. And we can clear the path for more people by building better systems of opportunity in our schools, teams, and workplaces. Many writers have chronicled the habits of superstars who accomplish great things. This book breaks new ground by revealing how anyone can rise to achieve greater things. The true measure of your potential isn't the height of the peak you reach, but how far you climb to get there"--